Four Histories about Early Dutch Football, 1910-1920 - Peircey, Nicholas (UCL Press, 2016)
What is the purpose of history today, and how can sporting research help us understand the world around us? In this stimulating book, Nicholas Piercey constructs four new histories of early Dutch football, exploring urban change, club members, the media, and the diaries of Cornelis Johannes Karel van Aalst, a stadium director, to propose practical examples of how history can become an important democratic tool for the 21st century.